Conocimientos y actitudes sobre tuberculosis del personal de salud de Belén, Gualel, Hospital Básico de Vilcabamba, Malacatos, Motupe, Obrapía, Pichic y Yangana, del Distrito 11D01 Loja, periodo mayo-octubre 2016. - Lozano Rengel, Nelly Karina (2017)
Tuberculosis is a public health problem worldwide, it is estimated that a third of the population is infected with the Mycobacterium tuberculosis bacillus. In 2015, the estimated number of new cases was 10.4 million, of which 1.8 million died because of this, without counting about 400 thousand more among those infected with Tuberculosis/HIV coinfection. The current research aims to establish the level of knowledge and attitudes regarding the prevention, diagnosis and treatment of tuberculosis of operational health personnel in health centers belonging to District 11D01, Loja. For this, a descriptive, cross-sectional study was presented, where the study area consisted of 8 health units, and the universe and the sample, 71 people, to whom a questionnaire was applied with 15 multiple choice questions and one test, based on the Likert scale, with 15 proposals, tools that allowed to collect the necessary information, which was analyzed, tabulated and represented by statistical graphs. It was found that 52% of the health personnel surveyed had a high level of knowledge, 37% were regular and 11% were low; in terms of prevention, 86% of staff expressed acceptance, 11% were indifferent, and 3% rejected; in terms of diagnosis, 93% of the staff showed acceptance and 7% were indifferent. Regarding attitude towards treatment, 80% presented acceptance, 18% were indifferent and 1% rejected the proposed measures. Based on the results of the research, a proposal for standards of prevention of tuberculosis established by the Ministry of Public Health was strengthened, taking into account the scientific evidence provided. Keywords: Tuberculosis; Knowledge; Attitudes;